2002
DOI: 10.1002/app.11660
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear viscoelasticity of carbon black filled elastomers: Use of complementary rheological characterizations

Abstract: ABSTRACT:The viscoelastic properties of filled elastomers (uncured styrene-butadiene rubber filled with carbon black) were investigated with two shear rheometers specially designed for the characterization of complex polymer systems. A torsional strain-controlled rheometer [i.e., a rubber process analyzer (RPA)] was used in dynamic and relaxation modes for measuring the storage and loss moduli and the relaxation modulus. A stress-controlled sliding cylinder rheometer (SCR) was operated for the measurement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…However, the ratio of the real contact area is less than of order 10 −4 and effective strain at the microscale, ε = A 0 ε 0 /A, is estimated to be of order unity. Strain sweep testing in general shows that the dynamic storage modulus of carbon-black-filled rubber decreases less than half under such large strain (Payne, 1964, Payne, 1965, Barrés et al, 2003, which is acceptable for our numerical assessment that the simulated rubber coefficient β < 1/2 is in good agreement with µ exp . The complete prediction of µ h requires the true complex elastic modulus as a function of the strain amplitude changing across the multiple sizes of asperities.…”
Section: Discussionsupporting
confidence: 64%
“…However, the ratio of the real contact area is less than of order 10 −4 and effective strain at the microscale, ε = A 0 ε 0 /A, is estimated to be of order unity. Strain sweep testing in general shows that the dynamic storage modulus of carbon-black-filled rubber decreases less than half under such large strain (Payne, 1964, Payne, 1965, Barrés et al, 2003, which is acceptable for our numerical assessment that the simulated rubber coefficient β < 1/2 is in good agreement with µ exp . The complete prediction of µ h requires the true complex elastic modulus as a function of the strain amplitude changing across the multiple sizes of asperities.…”
Section: Discussionsupporting
confidence: 64%
“…Many researchers have investigated into the influences of CB on the physical [1, 2], thermal [3–6], electrical [7], rheological and viscoelastic [8–10], and vulcanization [1, 11, 12] properties of filled compounds. Using rubber process analyzer, Barres et al [10] showed that the relaxation modulus of a filled rubber compound has a good agreement with the viscoelastic integral model. Other researchers [5] measured the hysteresis loss of NR and SBR compounds and found that the magnitudes of hysteresis loss increase with loading of carbon black.…”
Section: Introductionmentioning
confidence: 99%
“…A similar observation was reported for the rheological behavior of other filled polymer systems. [24] The network structure of the LDPE/PU blend emanates from the enormous entanglement point of the amorphous zone of LDPE and millable PU elastomer. This network structure is sustained despite the large deformation in the strain sweep experiment (in case of the LDPE/millable PU blend).…”
Section: Evidence Of Deformation Of Entanglement Networkmentioning
confidence: 99%